Factors affecting infection control measures performed by dental workers - Hsin-Chung Cheng; Yu-Chun Yen; Amy Ming-Fang Yen; Sam Li-Sheng Chen (Elsevier, 2023)
Background/purpose: An understanding of self-protection related factors is important for dental infection control. This study aimed to investigate factors associated with personal self-protection in infection control among dental care workers. Materials and methods: A cross-sectional survey with self-report questionnaire was conducted between Jan and Dec, 2018.275 dentists and 298 dental assistants were enrolled from randomly selected dental care settings. Results: Compliance with wearing hair caps, facial masks, and hand washing is not as high as oral masks and gloves (over 90%). For dentists, the level of clinical setting (aOR = 3.1, P < 0.001) and the correct use of disinfectants for impression materials (aOR = 2.0, P < 0.05) were associated with hair cap wearing. Gender (aOR = 0.15, P < 0.05) and correct use of indicator during sterilization (aOR = 2.9, P < 0.05) were associated with facial mask wearing. The correct use of indicator during sterilization (aOR = 2.4, P < 0.05) and disinfection for impression materials (aOR = 2.2, P < 0.05) were associated with hand washing. For dental assistants, longer work experience (aOR = 1.05, P < 0.05), working days (aOR = 1.82, P < 0.05), the correct use of disinfectants for impression materials (aOR = 2.4, P < 0.001), and the frequent use of gloves (aOR = 8.0, P < 0.05) were associated with facial mask wearing. The surface disinfection of working tables (aOR = 2.8, P < 0.001) and the frequent changing of gloves (aOR = 5.96, P < 0.05) were associated with hand washing. Conclusion: Gender, the length of work practice, and correct techniques for sterilization use were identified as major factors associated with compliance with self-protection in infection control among dental care workers.